The Influence of Leadership Style on Employee Performance in ‎Jordanian Banks: The Mediating Role of PerceivedOrganizational ‎Support - Al-Zu’bi , Sara Khaled; Ibrahim , Hadziroh; Ismail, Edora (International Journal of Accounting and Economics Studies, 2025)
This study aimed to identify the impact of leadership style, with its various elements ‎‎(transformational leadership and transactional leadership), on improving employee ‎performance in Jordanian commercial banks. The study also aimed to identify the ‎mediating role of perceived organizational support in determining the relationship between ‎leadership style and employee performance in the banks under study. The study population ‎consisted of Arab Bank, Jordan Ahli Bank, Jordan Capital Bank, and Jordan Commercial ‎Bank, where purposive sampling was used by publishing an electronic questionnaire (online ‎questionnaire) via the Google Form website to assistant managers, supervisors, and ‎executive directors; 356 responses were received. The data was subjected to statistical ‎analysis. The study concluded that the combined elements of leadership style had an impact ‎on improving employee performance in the Jordanian banks, given the presence of ‎perceived organizational support. The effect of perceived organizational support on the ‎relationship between transactional leadership style and employee performance was not ‎proven. The study recommended that the banking sector focus on inspiring, motivating, ‎and supporting its employees with a clear vision, personalized attention, and intellectual ‎stimulation. However, the banks need to develop a culture of perceived organizational ‎support‎.
Keywords: Leadership Style; Transformational Leadership; Transactional Leadership; Employee ‎Performance; Perceived Organizational Support